The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/cdd.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

RIP4 inhibits STAT3 signaling to sustain lung adenocarcinoma differentiation

Abstract: Loss of epithelial differentiation and extracellular matrix (ECM) remodeling are known to facilitate cancer progression and are associated with poor prognosis in patients with lung cancer. We have identified Receptor-interacting serine/threonine protein kinase 4 (RIP4) as a regulator of tumor differentiation in lung adenocarcinoma (AC). Bioinformatics analyses of human lung AC samples showed that poorly differentiated tumors express low levels of RIP4, whereas high levels are associated with better overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
(53 reference statements)
0
26
2
Order By: Relevance
“…Thus, activation of STAT3 by RIP4 and subsequent changes in STAT3‐regulated genes may play a role in skin inflammation. It is reported that RIP4 hinders STAT3 activation in lung cancer cells, reducing cancer differentiation . These results seem to be quite different to our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, activation of STAT3 by RIP4 and subsequent changes in STAT3‐regulated genes may play a role in skin inflammation. It is reported that RIP4 hinders STAT3 activation in lung cancer cells, reducing cancer differentiation . These results seem to be quite different to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…It is reported that RIP4 hinders STAT3 activation in lung cancer cells, reducing cancer differentiation. [46] These results seem to be quite different to our findings. In detail, STAT3 has two phosphorylation sites (tyrosine 705 and serine 727).…”
Section: Several Studies Have Reported Higher Levels Of Stat3contrasting
confidence: 99%
“…Receptor-interacting serine/threonine protein kinase 4 (RIP4) is an ankyrin repeatcontaining kinase that is in charge of keratinocyte differentiation and delays cell migration during wound healing. It has recently been found to be a likely regulator of tumor differentiation in LUAD and contributes to epithelial identity and differentiation (22). This study demonstrated that poorly differentiated tumors correlate with low expression of RIP4, whereas high expression correlates with better overall survival.…”
Section: Stat3mentioning
confidence: 54%
“…Cells from their in vitro studies associate reduced RIP4 expression with elevated activation of STAT3 signaling and had an overall increased capacity for tissue invasion. In comparison, overexpression of RIP4 inhibited STAT3: after tail vein injections of RIP4overexpressing cells, tissue invasion and tumor formation were reduced, which was restored by co-expression of STAT3 (22).…”
Section: Stat3mentioning
confidence: 93%
“…STAT3 can regulate the growth cycle of cancer cells by affecting the expression of cyclin D1 and P27 [18]. Cyclin D1 and P27 are closely related to pathophysiological processes such as cell proliferation and apoptosis inhibition [19].…”
Section: Introductionmentioning
confidence: 99%